Measles and mumps outbreaks in Lebanon: trends and links - El Zarif, Talal (BMC Infect Dis, 2020)
BACKGROUND: Lebanon has experienced several measles and mumps outbreaks in the past 20 years. In this article, a case-based surveillance of both measles and mumps outbreaks in Lebanon was carried out in an attempt to outline factors contributing to the failure of elimination plans and to provide potential solutions. The relationship between the outbreaks of both diseases was described and explored. METHODS: A retrospective descriptive study of confirmed cases of measles and mumps in Lebanon between 2003 and 2018 collected from the Lebanese Ministry of Public Health Epidemiological Surveillance Unit public database was carried out. The information collected was graphically represented taking into consideration dates of reported cases, age groups affected, and vaccination status. RESULTS: The mean number of measles cases was 150.25 cases/year in the 1–4 years age group, 87 cases/year in individuals aging between 5 and 14, and 63.68 cases/year in those > 14 years old. In the latter group, only 18.05% were unvaccinated. The mean number of mumps cases was 30.4 cases/year in the < 4 year age group and 53.8 cases/year in the 10–19 years age group. During the study period, every spike in measles cases was followed by a similar spike in mumps. 9.66% of measles cases occurred in individuals who received at least 2 doses of the vaccine, 52.26% in the unvaccinated, and 38% in those whose vaccination status was undetermined. CONCLUSIONS: Measles in Lebanon is a disease of the pediatric population, but adults remain at risk. Outbreaks of mumps followed those of measles and were mainly among adolescents. Presence of a large number of Syrian refugees in the country may further complicate the situation. Vaccination activities need to be intensified.